2021
DOI: 10.1186/s13068-021-02054-1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding the effects of lignin structural characteristics on enzymatic hydrolysis

Abstract: Enzymatic hydrolysis of lignocellulose for bioethanol production shows a great potential to remit the rapid consumption of fossil fuels, given the fact that lignocellulose feedstocks are abundant, cost-efficient, and renewable. Lignin results in low enzymatic saccharification by forming the steric hindrance, non-productive adsorption of cellulase onto lignin, and deactivating the cellulase. In general, the non-productive binding of cellulase on lignin is widely known as the major cause for inhibiting the enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(51 citation statements)
references
References 172 publications
(219 reference statements)
0
50
1
Order By: Relevance
“…The effect of acetylation on reduced enzymatic hydrolysis of biomass from woods, in general, has been reviewed by Pawar et al [ 53 ], and has specifically been reported for β-mannanases, including Tr Man5A [ 54 , 55 ]. In addition, thermal treatment of lignocellulose may generate lignin-aggregates that bind and inhibit enzymes such as cellulases [ 29 , 35 , 56 ]. However, if this occurred in the present case, it was probably a less pronounced contributing effect with the TMP-AcGGM, since it was purified with SEC [ 40 ], which likely separated such aggregates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of acetylation on reduced enzymatic hydrolysis of biomass from woods, in general, has been reviewed by Pawar et al [ 53 ], and has specifically been reported for β-mannanases, including Tr Man5A [ 54 , 55 ]. In addition, thermal treatment of lignocellulose may generate lignin-aggregates that bind and inhibit enzymes such as cellulases [ 29 , 35 , 56 ]. However, if this occurred in the present case, it was probably a less pronounced contributing effect with the TMP-AcGGM, since it was purified with SEC [ 40 ], which likely separated such aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…Softwood-based SSL contains AcGGM and its degradation products, but is also rich in lignin and lignin-derived compounds such as lignosulfonates (LS) [ 25 , 26 , 27 ]. It is known that the presence of lignin results in lower enzymatic cellulose saccharification yields due to steric hindrance, non-productive binding of cellulases onto lignin, and enzyme deactivation [ 28 , 29 ]. The current understanding of the mechanism involved in enzyme-lignin interaction is largely based on the interaction of insoluble lignin with cellulases [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the natural aromatic polystructure, lignin (which can mainly be extracted from softwood, hardwood, and grass, and the model lignin structures is shown in Fig. 1 [ 1 ]) has been regarded as a sustainable alternative to fossil-derived resources to provide valuable biochemicals [ 2 7 ]. Interunits of lignin are connected by C–O and C–C bonds (such as β-O-4, β–β, and β-5, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the development of technologies to solve this problem is expected to reduce the ame retardancy of biomass and increase the yield of extractable cellulose and fermentable sugar for pulp or biofuel production. In recent years, biotechnological approaches to modulate lignin content have been used to optimize plant biomass in various industries (Liu, et al 2020;Yuan, et al 2021). The study of lignin biosynthesis and its function has therefore had signi cant impacts on the industry, agriculture, and other human activities.…”
Section: Introductionmentioning
confidence: 99%